2022
DOI: 10.1111/cts.13259
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of depot‐specific regulation of all‐trans‐retinoic acid biosynthesis in human adipose tissue

Abstract: The prevalence of obesity continues to rise, underscoring the need to better understand the pathways mediating adipose tissue (AT) expansion. All-trans-retinoic acid (atRA), a bioactive vitamin A metabolite, regulates adipogenesis and energy metabolism, and, in rodent studies, aberrant vitamin A metabolism appears a key facet of metabolic dysregulation. The relevance of these findings to human disease is unknown, as are the specific enzymes implicated in vitamin A metabolism within human AT. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 150 The enzyme ALDH1-A is involved in all-trans RA biosynthesis in a depot-specific manner in human vWAT. 151 …”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 99%
“… 150 The enzyme ALDH1-A is involved in all-trans RA biosynthesis in a depot-specific manner in human vWAT. 151 …”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 99%
“…Such translational studies have shown higher mRNA expression of RBP4 and ALDH1A1 in adipose tissue from participants with obesity relative to normal weight controls (Klöting et al 2007, Landrier et al 2017. Recently, the formation velocity of atRA and the key enzymes responsible for atRA biosynthesis were shown to differ between human s.c. and omental adipose tissue (Rubinow et al 2022). In another study, lower hepatic concentrations of retinol and retinyl esters and diminished RARβ expression were found to be associated with NAFLD severity (Trasino et al 2015).…”
Section: Systemic Vitamin a Metabolismmentioning
confidence: 90%
“…Importantly, the specific enzymes contributing to retinoid metabolism vary across tissues and cell types (Arnold et al 2015a,b, Czuba et al 2021 and have not been fully defined in human tissues. Only recently, for example, were the key atRA-synthesizing enzymes identified within human liver (Zhong et al 2021) and human omental and s.c. adipose tissue (Rubinow et al 2022). Notably, while 13-cis-RA was readily quantifiable in human liver, it has not been detected in mouse liver (Zhong et al 2019).…”
Section: Vitamin a Homeostasismentioning
confidence: 94%
“…The key role of ALDH1a2 in development is underscored by the report of humans with two different missense variants in ALDH1a2 that result in a severe, multiple congenital anomaly syndrome with neonatal lethality (Beecroft et al 2021). Other members of this ALDH1A family include ALDH1a1, which contributes to the synthesis of RA in adipose tissue (Elizondo et al 2009, Haenisch et al 2021, Rubinow et al 2022, and ALDH1a3, which is active in cardiac atrial appendage progenitor cells (Puttini et al 2018). As might be expected, higher RA levels generally reduce the expression of ALDH1a2 in RA-target cells (Billings et al 2013).…”
Section: Oxidation Of Retinaldehyde (Ral) To Retinoic Acid Regulates ...mentioning
confidence: 99%